2023
DOI: 10.1177/1934578x231153733
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking, and Cytotoxic Evaluation of Fluorinated Podophyllotoxin Derivatives

Abstract: Objective: The study was conducted to evaluate the in vitro and in silico anticancer activity of fluorinated podophyllotoxin derivatives. Methods: Microwave-assisted multicomponent reactions were carried out in an Anton Paar Microwave Synthetic Reactor Monowave 400 in order to synthesize fluorinated podophyllotoxin derivatives. These products were identified by spectral analysis and evaluated for their cytotoxicity against 4 types of human cancer cell lines (KB, HepG2, A549, and MCF7), as well as human embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Besides that, all synthesized compounds were also evaluated for their cytotoxic activities against human cancer cell lines, namely human epidermoid carcinoma cancer cell line (KB), human lung cancer cell line (A549) and human hepatoma carcinoma cancer cell line (HepG2) by MTT (3-[4,5-di-methylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay, 71,72 with ellipticine as a reference. The results indicated that all synthesized products have shown no cytotoxic activity against selected cancer cell lines with IC 50 > 32 µg/mL (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, all synthesized compounds were also evaluated for their cytotoxic activities against human cancer cell lines, namely human epidermoid carcinoma cancer cell line (KB), human lung cancer cell line (A549) and human hepatoma carcinoma cancer cell line (HepG2) by MTT (3-[4,5-di-methylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay, 71,72 with ellipticine as a reference. The results indicated that all synthesized products have shown no cytotoxic activity against selected cancer cell lines with IC 50 > 32 µg/mL (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…37 Several hybrid compounds of 4-aza-podophyllotoxin with heterocycles have been developed and evaluated the anticancer activity. [38][39][40][41] For instance, Kamal et al, has prepared a series of 4-azapodophyllotoxin with heterocycles including benzothiazole-podophyllotoxin hybrids 6, pyrimidine-podophyllotoxin hybrids 7, and, indole-podophyllotoxin hybrids 8 which have inhibited tubulin polymerization, induced cell cycle arrest at G2/M phase and caspase-3 dependent apoptotic cell death in non-small lung A549 cell line. 33 Pyrazole-podophyllotoxin hybrids which have been synthesized by Magedov et al, have showed apoptosis induction in cancerous Jurkat cells even aer a short 24 h exposure.…”
Section: Introductionmentioning
confidence: 99%